Effect of Replacement of Commercial Ration with Mung Bean Sprout Waste Flour to the Male Bali Duck Digestion System - A., Maulana; Suasta, I M.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
Waste of mung bean sprouts is a part of mung bean sprouts that are not utilized in the production process, even usually wasted. This study aims to determine the effect of replacement of commercial rations with fermented mung bean sprout flour on the digestive system of male Bali ducks. This study uses a completely randomized design (CRD) with three treatments and five replications. The treatment given is; P0 (100% commercial ration), P1 (replacement of 12.5% commercial ration with fermented mung bean sprout flour) and P2 (replacement of 25% commercial ration with fermented mung bean sprout waste flour). The variables observed in this study were percentage of crop weight, percentage of proventriculus weight, percentage of ventricular weight, percentage of liver weight, percentage of pancreatic weight, percentage of bile weight, percentage of small intestine weight and length of small intestine. The results showed that the replacement 12.5% ??and 25% of commercial rations with fermented mung bean sprouts flour significantly (P<0.05) increased the percentage of crop weight with P1 and P2 respectively by 40.90% and 86.36 % higher than the commercial ration treatment 100% (P0), but not significantly different (P>0.05) to the percentage of percentage of proventriculus weight, percentage of ventricular weight, percentage of liver weight, percentage of pancreatic weight, percentage of bile weight, percentage of small intestine weight and length of small intestine. Based on the results of the study, it can be concluded that the replacement of 12.5% ??and 25% commercial rations with fermented mung bean sprouts flour increases the percentage of crop weight, but gives the same results to the percentage of proventriculus weight, percentage of ventricular weight, percentage of liver weight, percentage of pancreatic weight, percentage of bile weight, percentage of small intestine weight and length of small intestine.   Key word         : Waste of green bean sprouts, male bali ducks, fermentation, digestive system